Uji adaptasi pertumbuhan beberapa varietas sorgum di lahan pasir pantai Desa Dampek, Kabupaten Manggarai Timur, Nusa Tenggara Timur - Muhammad Noor Ariefin; Rizki Adiputra Taopan; Nella Angelina Simanjuntak; Devi Liana; Tri Astuti; Defiyanto Djami Adi (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2023)
Sorghum has a high adaptability in its growth in dry and marginal lands. Coastal sandy land is characterized by sandy texture and rapid water drainage. Developing sorghum in coastal sandy lands can be a utilization of land resources to produce local food materials in East Nusa Tenggara. This research aims to determine the growth respons and yield of various sorghum varieties in coastal sandy lands. The research was conducted in Dampek Village, East Manggarai, East Nusa Tenggara. The research used a Complete Randomized Block Design (CRBD) method with one factor, which is sorghum varieties. The sorghum varieties used were Bioguma-1, Suri-3, and Super-2. The observed research parameters included plant height, stem diameter, number of leaves, and panicle weight. The research results were analyzed using Analysis of Variance (ANOVA) at a significant level of 5%. Based on the study results, it is known that all three sorghum varieties can provide a good growth response for each parameter. The three sorghum varieties, Suri-3, Bioguma-2, and Super-2, can adapt well to coastal sandy lands in Dampek Village, East Manggarai Regency, East Nusa Tenggara.